A critique on the rationality debate. - Lin, Cherie Xinyi. (2012)
The study examines the various limitations associated with using the normativism framework within the rationality debate. These limitations include the presence of multiple norms which leads to the resultant illogical “is-ought” inference (invoked to justify the usage of a particular normative model), and certain methodological concerns such the prior rule bias and the interpretation bias. In addition to the inadequacies of the normativism framework, the study also addresses the importance of cultural influence on cognitive strategies in areas such as overconfidence and risk preference. This discussion helps to highlight the importance of cultural elements in cognition, which is noticeably disregarded by many researchers within the rationality debate. Lastly, the need for the field to progress beyond studying reasoning patterns in abstract experimental tasks, and to observe how humans actually reason in real-life situations has also being explored.